Jaringan Kerjasama Perpustakaan Sekolah - Aldi Priatmana; Siti Masitoh; Adelia Nur Annisa; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Meeting the information demands of users absolutely requires collaboration between libraries. The purpose of this research is to find out the value and necessity of library collaboration as well as the challenges that must be understood in order to successfully complete this collaborative activity. This essay is organized logically and is presented based on various sources. Because it is expected that no one library has a complete collection, cooperation with other libraries is needed, so the principle of collaboration between libraries is practiced. In addition, the following library collaboration tools can be used in collaboration: index, abstract, master catalog, magazine master catalog, bibliography, and master catalog. School libraries still face various challenges when trying collaborative activities. Keywords: Network; Cooperation; Library